Flicker Measurement and Grey Disaster Prediction of Grid-connected Wind Turbines - Zhanqiang Zhang; Keqilao Meng; Li Zhang (Universitas Ahmad Dahlan, 2015)
Grid-connected operation of large-scale wind turbines(WTs) will have an impact on power quality of electric power systems. Therefore, on the basis of analyzing the International Electrotechnical standard IEC 61400-21, we described the measurement, evaluation method of the flicker of WTs and proposed the method of grey disaster prediction.Active power, reactive power, flicker coefficient and flicker severity of the WTs were tested on the actual wind farm according to the IEC 61400-21 standard. We believed that the flicker severity was a disaster, so used the grey disaster prediction to predict the occurrence time of excessive flicker.Analysis of the test data of flicker was necessary,which could determine the Upper disaster threshold of the flicker.The disaster sequence was made up of the excessive flicker values. The date sequence was extracted from the disaster sequence. Establishing GM (1,1) model for the date sequence was to predict the future disaster date sequence.The experimental results showed that the relative accuracy of the disaster prediction model reached 94.87%, which was suitable for long-term flicker disaster prediction.